The Affordable Care Act and Health Insurance Markets Simulating the Effects of Regulation - Eibner, Christine (RAND Corporation, 2013)
In this report, the authors estimate the effects of the Affordable Care Act on health insurance enrollment and premiums for ten states (Florida, Kansas, Louisiana, Minnesota, New Mexico, North Dakota, Ohio, Pennsylvania, South Carolina, and Texas) and for the nation overall, with a focus on outcomes in the nongroup and small group markets.